A controlled trial of intravenous immunoglobulin in multifocal motor neuropathy. Issue 4 (December 2013) - Hahn, Angelika F.; Beydoun, Said R.; Lawson, Victoria; ,; Oh, MyungShin; Empson, Victoria G.; Leibl, Heinz; Ngo, Leock Y.; Gelmont, David; Koski, Carol L.
Abstract Intravenous immunoglobulin (IVIG) has become the standard treatment for multifocal motor neuropathy (MMN) based on limited data. To critically assess the efficacy, safety, and tolerability of 10% liquid IVIG (IVIG), 44 adults with MMN were randomized 1 : 1 to either double‐blind treatment of IVIG followed by placebo for 12 weeks each or the reverse. Open‐label IVIG was administered for 12 weeks at the beginning and end of the study for clinical stabilization, and between double‐blinded periods to prevent a carry‐over effect. To avoid potential worsening, switching to open‐label IVIG was permitted if deterioration occurred during blinded treatment. Mean maximal grip strength of the more affected hand declined 31.38% during placebo and increased 3.75% during IVIG (p = 0.005). In 35.7% of participants, Guy's Neurological Disability scores for upper limbs worsened during placebo and not during IVIG, whereas the converse was true in 11.9% (p = 0.021). Sixty‐nine percent (69.0%) switched prematurely from placebo to open‐label IVIG and 2.4% switched from blinded to open‐label IVIG (p < 0.001). One serious adverse reaction (pulmonary embolism) and 100 non‐serious reactions (69 mild, 20 moderate, and 11 severe) to IVIG occurred. IVIG was effective in improving disability and muscle strength, and was safe and well tolerated in adults with MMN.